Implementasi E-Learning dengan Adaptasi Game Based Learning di SMP untuk Meningkatkan Pemahaman Konsep dan Keterlibatan Aktif Siswa - Choirul Kurniawan; Ismatul Azizah; Napfiah, Siti (Universitas Insan Budi Utomo, 2025)
Electronic Learning (E-Learning) is a learning process that utilizes electronic media, particularly the internet, as the primary system in teaching and learning activities. This study aims to describe the implementation of e-learning with game-based learning adaptations in the form of session-based gamification challenges in junior high schools. Another goal of this research is to evaluate the impact of this method on improving students' conceptual understanding and encouraging their active engagement during the learning process. Furthermore, this study seeks to identify the factors that support the successful implementation of gamification and to explore the challenges that may arise during the learning process. The method used in this research is classroom action research (CAR). The indicators of implementing e-learning with game-based learning adaptation in the form of session-based gamification challenges include conceptual understanding and active engagement. Conceptual understanding is measured through students' ability to explain concepts, solve problems, apply concepts, and show improvement in evaluation results. Active engagement is observed from participation in discussions, involvement in gamification, activity on the e-learning platform, and students' learning motivation. The study was conducted on fraction material at SMP Taman Siswa Turen, Malang Regency. This study involved 8th-grade students as its subjects, with a total of 20 students tasked with completing questions prepared in the Kahoot application. Based on the results of the study, it was found that prior to the implementation of gamification on this material, students' understanding of fraction concepts was relatively low, particularly in fraction operations. Students often struggled to identify solution steps and frequently made calculation errors. This highlights the need for a more interactive approach to enhance their understanding.